Novel materials through Nature's catalysts. Issue 8 (October 2015) - Richter, Michael; Schulenburg, Cindy; Jankowska, Dagmara; Heck, Tobias; Faccio, Greta
<x xml:space="preserve">Abstract</x> The use of enzymes in materials science allows the development of unique and innovative functional materials. As biomolecules, enzymes can provide exceptional features such as substrate specificity, rate acceleration, regio-, chemo-, and stereoselectivity within catalyzed reactions. Many enzymes are suitable for biomaterials modification because of their natural origin or because they catalyze a desired reaction between non-natural substrates. In their native form, or after tailoring by genetic engineering, enzymes can complement the traditional approaches of materials science by following Nature principles. Multiple technologies involve enzymes in the fabrication and processing of materials, such as direct enzymatic treatment of materials and the assembly of novel bio-hybrid materials. In this review we highlight the most recent applications of enzymes by illustrating selected examples from the last 3 years, and indicate future trends in the field of materials science.